A comprehensive review of castor oil‐derived renewable and sustainable industrial products. Issue 2 (27th October 2022) - Singh, Shikha; Sharma, Sumit; Sarma, Saurabh Jyoti; Brar, Satinder Kaur
Abstract: Castor oil is one important raw material that could serve as a renewable feedstock for industries in the age of exhausting fossil fuels. The chemical composition of oil and the structure of hydroxyl fatty acid are responsible for its unique physicochemical properties. The oil has diverse applications from pharmaceuticals to polyamides, from the manufacturing of ski boots to durable frames, and from lubricants to laxatives. The present review gives an insight into the physicochemical properties of castor oil and its application. The oil is used for the production of a great variety of its derivatives. Out of many derivatives of castor oil, four are produced and utilized at a larger scale. The names of the four derivates are ricinoleic acid, sebacic acid, undecylenic acid, and γ‐decalactone. The review will aim toward an insight into the evolved techniques for the manufacturing of these derivatives of castor oil, the biotechnological route of production, and metabolic engineering approaches. Though the industrial significance of castor oil and its derivatives had been known for ages, methods for their production are continuously changing.